Omega-3 fatty acids, inflammation and angiogenesis: basic mechanisms behind the cardioprotective effects of fish and fish oils - Massaro, M.; Scoditti, E.; Carluccio, M. A.; Campana, M. C.; De caterina, R. (Cellular and Molecular Biology, 2010)
Atherosclerosis is now widely accepted to be an inflammatory disease, characterized by degenerative as well as proliferative changes and extracellular accumulation of lipid and cholesterol, in which an ongoing inflammatory reaction plays an important role both in initiation and progression/destabilization, converting a chronic process into an acute disorder. Neovascularization has also been recognized as an important process for the progression/destabilization of atherosclerotic plaques. In fact, vulnerable atherosclerotic plaques prone to rupture are characterized by an enlarged necrotic core, containing an increased number of vasa vasorum, apoptotic macrophages, and more frequent intraplaque haemorrhage. Various functional roles have been assigned to intimal microvessels, however the relationship between the process of angiogenesis and its causal association with the progression and complications of atherosclerosis are still challenging and controversial. In the past 30 years, the dietary intake of omega-3 (n-3) polyunsaturated fatty acids - mainly derived from fish - has emerged as an important way to modify cardiovascular risk through beneficial effects on all stages of atherosclerosis, including plaque angiogenesis. This review specifically focuses on the modulating effects of n-3 fatty acids on molecular events involved in early and late atherogenesis, including effects on endothelial expression of adhesion molecules, as well as pro-inflammatory and pro-angiogenic enzymes. By accumulating in endothelial membrane phospholipids, omega-3 fatty acids have been shown to decrease the transcriptional activation of several genes through an attenuation of activation of the nuclear factor-ÎºB system of transcription factors. This occurs secondary to decreased generation of intracellular reactive oxygen species. This series of investigations configures a clear example of nutrigenomics - i.e., how nutrients may affect gene expression, ultimately affecting a wide spectrum of human diseases.